Review Of Islamic Law Regarding Beliefs About The Hereditary Tradition Of Providing 41 Kinds Of Wadai/Cakes In The Month Of Safar - Rusdiyah, Rusdiyah; Nurhidayah, Nurhidayah; Aziza, Shilva Nur Aziza; Al Jinan, Muhamad Fatih Al Jinan; Sa'adah, Sa'adah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
This research relates to the belief in the hereditary tradition of providing 41 kinds of wadai or cakes in the month of Safar which is still practiced by some Banjar people. The 41 kinds of wadai or cakes are one of the culinary specialties of Banjarmasin, South Kalimantan. The provision of 41 kinds of wadai or cakes is done in the month of Safar because people still believe that Safar is a month full of bad luck. The 41 kinds of wadai are held to ask for protection and keep people away from various misfortunes or calamities. The method used in this research is a field research method that still occurs in Banjar society and a qualitative approach with literature study, which refers to the literature on the issues studied. Wadai or 41 kinds of cake is one of the requirements for various traditional events in Banjar society, one of which is the tradition of providing this wadai in the month of Safar which is believed to provide protection for the community. This study also aims to determine the view of Islamic law regarding the belief in the hereditary tradition of providing 41 kinds of wadai in the month of safar.